Intercultural communicative competence in the development of students’ linguistic skills - Lysiuchenko, Olena; Sydorenko, Yuliia; Oleksiienko, Larysa; Lysenko, Tetiana; Hulych, Mariia (Linguistics and Culture Review, 2021)
Intercultural communicative competence (ICC) is a component of the general concept of communicative competence, which refers to the ability to establish effective communication with representatives of different social-cultural regions. The role of ICC is growing significantly with the intensification of globalization processes. The purpose of the present academic paper is a comprehensive research of intercultural communicative competence of students-philologists while studying a foreign language at university. To achieve the purpose outlined, the following methods have been used, namely: analysis; synthesis; generalization; ascertaining experiment; the method of formative experiment; comparison. As a result of the research conducted, a diagnostic model has been developed in order to determine the level of ICC formation in students of foreign philology (based on English); a tactic of stimulating the initially diagnosed level of students’ ICC by conducting a formative experiment with subsequent secondary diagnostics for measurement of efficiency of the offered technique. It has been determined that the factors that have influenced the results are as follows: the complexity of the methodologies applied, the duration of the formative experiment, the intensity of work on improving ICC, individual features of participants (motivation, attitude to learning in general, etc.).